Вплив рівня виробничих ресурсів на якість ремонту машин - Дашивець, Галина Іванівна; Дашивец, Галина Ивановна; Dashyvets, Halyna; Паніна, Валерія Валеріївна; Панина, Валерия Валерьевна; Panina, Valeriia; Бондар, Андрій Миколайович; Бондарь, Андрей Николаевич; Bondar, Andrii (My University, 2021)
UK: Основна мета – дослідження факторів рівня виробничих ресурсів сервісного підприємства, що впливають на якість ремонту машин. В статті для аналізу процесів підприємства технічного сервісу і розробки плану заходів щодо підвищення ефективності його діяльності було використано «дерево цілей». Виявлені комплексні фактори рівня виробничих ресурсів, від яких залежить якість ремонту машин. Виконано ранжування всіх показників, за результатами експертної оцінки були визначені коефіцієнти вагомості для факторів, що входять в дерево цілей. Побудовані діаграми коефіцієнтів вагомості показників. Розглянуті фактори дозволили сформулювати основні напрямки підвищення якості ремонту. EN: The main goal is to study the factors of the level of production resources of the service enterprise that affect the quality of machine repair. The article discusses strategies for product and service quality management. The works of domestic and foreign scientists who studied the quality system are analyzed. The main directions of the complex system of the process of improving the quality of agricultural machinery are formulated. The "Goal Tree" was used to analyze the processes of the technical service enterprise and develop an action plan to increase the efficiency of its activities. The stages of the program-target approach are formulated. Complex factors of the level of production resources on which the quality of machine repair depends are revealed: technological base, engineering preparation of production, labor force. The ranking of all indicators was performed, based on the results of the expert assessment, the weighting factors for the factors included in the goal tree were determined. Diagrams of coefficients of weight of indicators are constructed. As a result, it was determined that the most important and fundamental condition for quality work is the availability of tools and objects of labor. In the first place in the technological base, experts put an indicator of the availability of technological equipment; organization of work of executors – in a complex factor of engineering preparation of production; labor discipline and technology – in a comprehensive indicator of the workforce. The considered factors allow to formulate the basic directions of increase of quality of repair, namely constant and continuous improvement of technological processes, increase of technical level of production and qualification of the personnel, development and application of new progressive methods of control and the analysis of quality of production, increase of culture of production, interest of workers. RU: Основная цель – исследование факторов уровня производственных ресурсов сервисного предприятия, влияющих на качество ремонта машин. В статье для анализа процессов предприятия технического сервиса и разработки плана мероприятий по повышению эффективности его деятельности было использовано «дерево целей». Обнаруженные комплексные факторы уровня производственных ресурсов, от которых зависит качество ремонта машин. Выполнено ранжирование всех показателей, по результатам экспертной оценки были определены коэффициенты весомости для факторов, входящих в дерево целей. Построенные диаграммы коэффициентов весомости показателей. Рассмотрены факторы позволили сформулировать основные направления повышения качества ремонта.
Influence of the level of production resources on the quality of repair of machines
Влияние уровня производственных ресурсов на качество ремонта машин
Keywords: управління якістю; «дерево цілей»; рівень виробничих ресурсів; експертна оцінка; коефіцієнт вагомості; діаграма; технологічна база; інженерна підготовка виробництва; робоча сила; quality management; "tree of aims"; level of productive resources; expert estimation; coefficient of ponderability; diagram; technological base; engineering preproduction; labour force; управление качеством; «дерево целей»; уровень производственных ресурсов; экспертная оценка; коэффициент весомости; диаграмма; технологическая база; инженерная подготовка производства; рабочая сила